LANGUAGE ANXIETY IN ENGLISH SPEAKING AMONG UZBEK UNIVERSITY STUDENTS - Zokirova Marjona Xislatjon qizi (НАУЧНЫЕ ИССЛЕДОВАНИЯ И ИННОВАЦИИ, 2025)
Annotation : This study investigates the phenomenon of language anxiety among Uzbek university students when speaking English. It examines the causes, manifestations, and effects of anxiety on oral communication skills. Using surveys and interviews, the research identifies key factors such as fear of making mistakes, lack of confidence, and negative classroom environments. The paper also explores strategies to reduce anxiety, including supportive teaching methods, peer collaboration, and increased exposure to authentic speaking opportunities. Findings highlight the importance of addressing affective factors to enhance English speaking proficiency and learner motivation.